If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 7) * 2 + 17 = 25 Reorder the terms: 3(7 + x) * 2 + 17 = 25 Reorder the terms for easier multiplication: 3 * 2(7 + x) + 17 = 25 Multiply 3 * 2 6(7 + x) + 17 = 25 (7 * 6 + x * 6) + 17 = 25 (42 + 6x) + 17 = 25 Reorder the terms: 42 + 17 + 6x = 25 Combine like terms: 42 + 17 = 59 59 + 6x = 25 Solving 59 + 6x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-59' to each side of the equation. 59 + -59 + 6x = 25 + -59 Combine like terms: 59 + -59 = 0 0 + 6x = 25 + -59 6x = 25 + -59 Combine like terms: 25 + -59 = -34 6x = -34 Divide each side by '6'. x = -5.666666667 Simplifying x = -5.666666667
| 1/2x=3 | | p=25 | | -3/4(12x-8)=-18 | | 20-4x=5x-35 | | a^2+2a+8=0 | | x-6=42 | | 4x+y=-20 | | 2p-1=3y+11 | | 29-H=207 | | 9x-4x+32=6x-21 | | 33=0+3y | | 3y-2y=8x | | y=3/5+9 | | y=2.5x-2 | | 21/p+1=8 | | a^2-2a+8=0 | | 15+(-4x-18)=9 | | 5n-7=3n-9 | | a/-6+8=12 | | 1-k=27 | | c/4=8 | | d/-2+5=7 | | 16-(9b+3)=4 | | 2(x-2)=16-3x | | -7x+y=-4 | | (2s+4)(2s-4)= | | 7x^2-5=2 | | x/4+10=34 | | 6x-2=-4x+7 | | -9=-20+a | | 17=2x-9 | | 4(x-2)+5x=10 |